The Thermal and Microstructural Effect of Plasticizing HMX-Nitrocellulose Composites. Issue 1 (2nd January 2018) - Yeager, John D.; Watkins, Erik B.; Higginbotham Duque, Amanda L.; Majewski, Jaroslaw
ABSTRACT: Thermal ignition via self-heating (cook-off) of cyclotetramethylene-tetranitramine (HMX)-containing plastic-bonded explosives (PBXs) is driven by the β → δ phase transition in the HMX, which is affected if not dominated by microstructure. Here, the HMX-binder interface and phase transition were studied for several variations of PBX 9404 (HMX with plasticized nitrocellulose [NC] binder). Neutron reflectometry was used to examine the interface under several conditions—pristine, after aging, and after thermal treatment. The initial interfacial structure depended on the plasticizer, but the interface homogenized over time. Thermal and optical analyses showed that all formulated materials had higher transition temperatures than neat HMX. This effect increased with NC content.